2011
DOI: 10.5539/ass.v7n9p124
|View full text |Cite
|
Sign up to set email alerts
|

Attributes, Environment Factors and Women Entrepreneurial Activity: A Literature Review

Abstract: Purpose: The purpose of this study is to examine the effect of individual attributes and business environment factors on the entrepreneurial activity of women entrepreneurs. Individual attributes such as education, working experience, attitude towards risk-taking, affect women entrepreneurial activity. Economic constraints such as lack of credit due to lack of asset collaterals and socio-cultural barriers, lack of savings due to low household income, and lack of labour skills due to low educational level also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
6
10
0
Order By: Relevance
“…Hence, H2 also supported. The result of H2 is congruent with previous studies (Geissler et al, 2012;Indarti et al, 2010;Kuzilwa, 2005;Maina, 2011;Mat & Razak, 2011;Román et al, 2013;Shastri & Sinha, 2010;Uddin & Bose, 2012). Additionally, the study found a significant and positive relation between entrepreneurial orientation and entrepreneurial intention (ß = 0.36; t = 5.620; p = 0.00) revealing strong support for H3.…”
Section: Structural Model Results (Pls Path With Moderator)supporting
confidence: 82%
See 2 more Smart Citations
“…Hence, H2 also supported. The result of H2 is congruent with previous studies (Geissler et al, 2012;Indarti et al, 2010;Kuzilwa, 2005;Maina, 2011;Mat & Razak, 2011;Román et al, 2013;Shastri & Sinha, 2010;Uddin & Bose, 2012). Additionally, the study found a significant and positive relation between entrepreneurial orientation and entrepreneurial intention (ß = 0.36; t = 5.620; p = 0.00) revealing strong support for H3.…”
Section: Structural Model Results (Pls Path With Moderator)supporting
confidence: 82%
“…Furthermore, authors have fully established that new venture only becomes possible as a result of the interaction that exists between environmental factors, personal characteristics and entrepreneurial behavior (Bird, 1988;Greenberg & Sexton, 1988;Stevenson & Jarillo, 1990;Suresh & Ramraj, 2012). In essence, Studies have empirically proved that environmental factors affect entrepreneurial process, thus the existence differences in terms of creation of new business, survival and growth (Geissler et al, 2012;Indarti et al, 2010;Kuzilwa, 2005;Maina, 2011;Mat & Razak, 2011;Román, Congregado, & Millán, 2013;Shastri & Sinha, 2010;Uddin & Bose, 2012). We therefore, hypothesized that: H2: Environmental factors will be positively related to entrepreneurial intention.…”
Section: Environmental Factor and Entrepreneurial Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Udida et al (2012) found that children from rich homes record poor academic performance in schools. Generally, this study supported previous studies in the field (Ekpe et al, 2011;Eweniyi, 2005;Azhar et al, 2013). Specifically, the study has made a striking and novel discovery that student's self-motivation (hard work) and rich parental socio-economic background are needed to achieve academic success; though self-motivation appears to be a more critical success factor.…”
Section: Discussionsupporting
confidence: 81%
“…Perceived behavioral control (PBC) or locus of control signifies a person's personality trait such as self-efficacy, self-confidence or beliefs. However, this study argues in line with previous studies (Ekpe et al, 2011;Shastri & Sinha, 2010;Vob & Muller, 2009) that, though someone may have positive self-confidence towards a behavior, an environment could hinder such a behavior. Aggregate of these factors could predict intention (I) and actual behavior (AB) (Ajzen, 1991).…”
Section: The Conceptual Frameworksupporting
confidence: 59%